IMPLEMENTATION OF FIREBASE IN THE DEVELOPMENT OF ANDROID-BASED QUEUE RESERVATION AND TREATMENT RECORD APPLICATIONS - Audy Fitri Ariani; Agung Brastama Putra; Tri Luhur Indayanti Sugata (Jurnal Sistem Informasi, 2025)
The development of an Android-based reservation and medical record management app is key to improving customer experience and operational efficiency in the beauty salon industry. This study explores the use of Firebase, offering features like Authentication, Firestore, Cloud Messaging, and Cloud Functions, to create a reliable mobile solution. Firebase enables real-time data management, secure authentication, and efficient notifications, enhancing both salon operations and customer experience. Developed with the Waterfall model and MVVM architecture, the app showed positive results in reservation and medical record management. Users can easily book appointments and access treatment history, with fast data transfer powered by Firebase. With response times of 120 ms for reads and 140 ms for writes, Firebase ensures seamless performance. The app reduced booking time by 79.91% compared to manual methods. Further development is recommended to include staff management and real-time analytics for optimized service and better customer insights.